Quantitatively Monitoring Bubble-Flow at a Seep Site Offshore Oregon: Field Trials and Methodological Advances for Parallel Optical and Hydroacoustical Measurements - Veloso-Alarcón, Mario E.; Urban, Peter; Weiss, Tim; Köser, Kevin; She, Mengkun; Greinert, Jens (Frontiers in Earth Science, 2022)
Two lander-based devices, the Bubble-Box and GasQuant-II, were used to investigate the spatial and temporal variability and total gas flow rates of a seep area offshore Oregon, USA. The Bubble-Box is a stereo camera equipped lander that records bubbles inside a rising corridor with 80Hz, allowing for automated image analyses of bubble size distributions and rising speeds. GasQuant is a hydroacoustic lander using a horizontally oriented multibeam swath to record the backscatter intensity of bubble streams passing the swath plain. The experimental set up at the Astoria Canyon site in about 500m water depth, aimed at calibrating the hydroacoustic GasQuant data with the visual Bubble-Box data for a spatial and temporal flow rate quantification of the site. For about 90h in total, both systems were deployed simultaneously and pressure and temperature data were recorded via a CTD as well. Detailed image analyses show a Gaussian-like bubble size distribution of bubbles with 0.6 to 6 mm in radius (mean 2.5 mm, std. dev. 0.25 mm); this is very similar to other measurements reported in the literature. Rising speeds ranged from 15 to 37 cm/s between 1 and 5 mm bubble sizes and are thus in parts slightly faster than reported elsewhere. Bubble sizes and calculated flow rates are rather constant over time at the two monitored bubble streams. Flow rates of these individual bubble streams are in the range of 544 to 1278 mm3/s. One Bubble-Box data set was used to calibrate the acoustic backscatter response of the GasQuant data enabling to calculate a flow rate of the ensonified seep area (~1700m2) that ranged from 4.98 to 8.33 l/min (5.38x106 to 9.01x106 CH4 mol/yr). Such flow rates are common for seep areas of similar size and as such this location classifies as a normally active seep area. For deriving these acoustically-based flow rates, the detailed data pre-processing considered echogram gridding methods of the swath data and bubble responses at the respective water depth. The described method uses the inverse gas flow quantification approach and gives an in-depth example of the benefits of using acoustic and optical methods in tandem.